MCST-Net: A Multi-Cross-Spatial Attention U-Net with Transformer Block for Skin Lesion Segmentation - Vu, Manh Hung (Springer Nature, 2024)
Lecture Notes in Networks and Systems (LNNS,volume 882); The 13th Conference on Information Technology and Its Applications (CITA 2024) ; pp: 397-408.